(untitled) (Research, Society and Development, 2023)
Brain–Computer Interfaces (BCIs) are specialized systems that allow users to control computer applications using their brain waves. With the arrival of consumer-grade electroencephalography (EEG) equipment, brain-controlled systems began to find fertile ground in mental training. One particular area that is gradually gaining attention is that of mindfulness training. In this paper, the results of a literature review of BCI-assisted mindfulness training using BCI’s are presented. The specific aim is to review the effects of BCIs embedded in mindfulness interventions on training metacognitive, emotional, and attention regulation skills. Papers published the last 10 years were reviewed. The results showed that the use of BCIs provides subjects the unique opportunity to self-regulate mental and emotional functions using the feedback derived from their own brain activity. Subjects were found to raise better awareness about the ways non-conscious operations influence mental and emotional states. It was observed that subjects by learning to deal with the neurofeedback within immersive worlds or with the aid of mobile devices can better develop awareness and self-regulation skills including inhibition and flexibility. Learning environments have been undergoing rapid change driven by the evolution and availability of digital technologies. In that vein, BCIs combined with mobiles and immersive technologies could support mindfulness as an innovative practice for cognitive, emotional, and metacognitive development. This study aims to contribute to the debate about the use of BCI-assisted mindfulness practices as proactive methods and training strategies for various target groups such as students, teachers, and workers to achieve well-being and peak performance.